Effects of lidocaine and magnesium sulfate in attenuating hemodynamic response to tracheal intubation: single-center, prospective, double-blind, randomized study - Mendonça,Fabricio Tavares (2017)
Abstract Background and objectives: Hemodynamic response to airway stimuli is a common phenomenon and its management is important to reduce the systemic repercussions. The objective of this study is to compare the efficacy of intravenous magnesium sulfate versus lidocaine on this reflex hemodynamics after laryngoscopy and tracheal intubation. Methods: This single-center, prospective, double-blind, randomized study evaluated 56 patients ASA 1 or 2, aged 18-65 years, scheduled for elective surgeries under general anesthesia with intubation. The patients were allocated into two groups: Group F received 30 mg·kg-1 of magnesium sulphate and Group L, 2 mg·kg-1 of lidocaine, continuous infusion, immediately before the anesthetic induction. Blood pressure (BP), heart rate (HR), and bispectral index (BIS) were measured in both groups at six different times related to administration of the study drugs. Results: In both groups there was an increase in HR and BP after laryngoscopy and intubation, compared to baseline. Group M showed statistically significant increase in the values of systolic and diastolic blood pressure after intubation, which was clinically unimportant. There was no difference in the BIS values between groups. Among patients receiving magnesium sulfate, three (12%) had high blood pressure versus only one among those receiving lidocaine (4%), with no statistical difference. Conclusion: Magnesium sulfate and lidocaine have good efficacy and safety for hemodynamic management in laryngoscopy and intubation.